Visual Intelligence Development In Online Learning For Children Affected By Social Distancing Due To Covid-19 - Nika Cahyati (STKIP Muhammadiyah Kuningan, 2021)
The development of visual intelligence in online learning for children affected by social distancing is now problematic. Learning that was originally face-to-face in the classroom has now turned into distance learning using online media. Online learning is still unfamiliar among young children. The purpose of this study was to determine the development of visual intelligence in online learning for children affected by social distancing due to covid-19 in PAUD IT Rumah Lebah Murung Pudak, Tabalong. The method used in this research is qualitative method. Research Setting in PAUD IT Rumah Lebah which is located at Komplek Citra Plambon Raya, Pembataan, Murung Pudak, Tabalong, South Kalimantan. The subjects of this study were 1 teacher and 1 student guardian. Data collection techniques using interviews via WhatsApp. The results showed that children's visual intelligence increased from the child's imagination. Children can draw interesting ideas like imagining covid-19 drawings. Where previously the child did not know in detail about covid-19 and the dangers of the virus.